Molecular biology of plant viruses (Kluwer Academic Publishers, 1999)
Molecular Biology of Plant Viruses analyzes, collates and reviews such published information. Additionally, it demonstrates the mechanisms of genetic variability; brings out the molecular basis of virus transport in plants and of virus transmission by vectors and of disease symptomatology; and discusses molecular biology of viroids and transgenic plants. It also treats the recently discovered genetic phenomenon of gene silencing and the gene-for-gene interactions between the hosts and plant viruses.